Comparative mitogenomic analysis of subterranean and surface amphipods (Crustacea, Amphipoda) with special reference to the family Crangonyctidae - Joseph B. Benito; Megan L. Porter; Matthew L. Niemiller (BMC Genomics, 2024)
Abstract Mitochondrial genomes play important roles in studying genome evolution, phylogenetic analyses, and species identification. Amphipods (Class Malacostraca, Order Amphipoda) are one of the most ecologically diverse crustacean groups occurring in a diverse array of aquatic and terrestrial environments globally, from freshwater streams and lakes to groundwater aquifers and the deep sea, but we have a limited understanding of how habitat influences the molecular evolution of mitochondrial energy metabolism. Subterranean amphipods likely experience different evolutionary pressures on energy management compared to surface-dwelling taxa that generally encounter higher levels of predation and energy resources and live in more variable environments. In this study, we compared the mitogenomes, including the 13 protein-coding genes involved in the oxidative phosphorylation (OXPHOS) pathway, of surface and subterranean amphipods to uncover potentially different molecular signals of energy metabolism between surface and subterranean environments in this diverse crustacean group. We compared base composition, codon usage, gene order rearrangement, conducted comparative mitogenomic and phylogenomic analyses, and examined evolutionary signals of 35 amphipod mitogenomes representing 13 families, with an emphasis on Crangonyctidae. Mitogenome size, AT content, GC-skew, gene order, uncommon start codons, location of putative control region (CR), length of rrnL and intergenic spacers differed between surface and subterranean amphipods. Among crangonyctid amphipods, the spring-dwelling Crangonyx forbesi exhibited a unique gene order, a long nad5 locus, longer rrnL and rrnS loci, and unconventional start codons. Evidence of directional selection was detected in several protein-encoding genes of the OXPHOS pathway in the mitogenomes of surface amphipods, while a signal of purifying selection was more prominent in subterranean species, which is consistent with the hypothesis that the mitogenome of surface-adapted species has evolved in response to a more energy demanding environment compared to subterranean amphipods. Overall, gene order, locations of non-coding regions, and base-substitution rates points to habitat as an important factor influencing the evolution of amphipod mitogenomes.